2022
DOI: 10.1093/eurheartj/ehac577
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 15 and cardiovascular risk: individual patient meta-analysis

Abstract: Aims Levels of growth differentiation factor 15 (GDF-15), a cytokine secreted in response to cellular stress and inflammation, have been associated with multiple types of cardiovascular (CV) events. However, its comparative prognostic performance across different presentations of atherosclerotic cardiovascular disease (ASCVD) remains unknown. Methods and results An individual patient meta-analysis was performed using data poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 37 publications
5
21
1
Order By: Relevance
“…Our data are in line with previous studies and with a recent large secondary patient-level analysis of eight randomized clinical trials across diferent forms of atherosclerotic cardiovascular disease, which observed a strong association between circulating GDF-15 and multiples types of cardiovascular events, including death and hospitalization for heart failure [3].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data are in line with previous studies and with a recent large secondary patient-level analysis of eight randomized clinical trials across diferent forms of atherosclerotic cardiovascular disease, which observed a strong association between circulating GDF-15 and multiples types of cardiovascular events, including death and hospitalization for heart failure [3].…”
Section: Discussionsupporting
confidence: 92%
“…Today, GDF-15 is considered as a marker of integrated underlying cardiovascular disease burden with higher circulating levels being associated with the presence of atherosclerotic cardiovascular disease. Very recently, a large study across multiple populations with atherosclerotic cardiovascular disease showed that circulating GDF-15 is a robust biomarker for assessing the risk of cardiovascular events and death beyond established clinical factors and biomarkers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analogous circumstances are also encountered in other disease. A recent meta-analysis of individual patients showed that GDF-15 demonstrated a strong and consistent independent association with cardiovascular death and heart failure across all presentations of atherosclerotic cardiovascular disease [ 45 ]. In a longitudinally sampled cohort of patients with multiple sclerosis, mean GDF-15 concentrations may serve as a biomarker for disease stability [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that GDF-15 may help to identify ACS patients at an increased bleeding risk who may benefit from a less aggressive antithrombotic treatment regimen following PCI. This is particularly important, as ACS patients’ bleeding events are associated with an increased risk of major adverse cardiac events (MACE) and death [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%